Cohort profile: a multicentre prospective validation cohort of the Chinese Acute-on-Chronic Liver Failure (CATCH-LIFE) study. Issue 1 (8th January 2021) - Qiao, Liang; Wang, Xianbo; Deng, Guohong; Huang, Yan; Chen, Jinjun; Meng, Zhongji; Zheng, Xin; Shi, Yu; Qian, Zhiping; Liu, Feng; Gao, Yanhang; Lu, Xiaobo; et al.
Abstract : Purpose: Acute-on-chronic liver failure (ACLF) is a clinical syndrome with high short-term mortality, unclear mechanism and controversial diagnosis criteria. The Chinese Acute-on-Chronic Liver Failure (CATCH-LIFE) study has been conducted in China to fill the gaps. In the first phase (the CATCH-LIFE investigation cohort), 2600 patients were continuously recruited from 14 national nationwide liver centres from 12 different provinces of China in 2015–2016, and a series of important results were obtained. To validate the preliminary results, we designed and conducted this multicentre prospective observational cohort (the CATCH-LIFE validation cohort). Participants: Patients diagnosed with chronic liver disease and hospitalised for acute decompensation (AD) or acute liver injure were enrolled, received standard medical therapy. We collected the participants' demographics, medical history, laboratory data, and blood and urine samples during their hospitalisation. Findings to date: From September 2018 to March 2019, 1370 patients (73.4% men) aged from 15 to 79 years old were enrolled from 13 nationwide liver centres across China. Of these patients, 952 (69.5%) had chronic hepatitis B, 973 (71.1%) had cirrhosis and 1083 (79.1%) complicated with AD at admission. The numbers and proportions of enrolled patients from each participating centre and the patients' baseline characteristics are presented. Future plans: A total of 12 months is required for each participant to complete follow-up. Outcome information (survival, death or receiving liver transplantation) collection and data cleansing will be done before June 2020. The data in the CATCH-LIFE validation cohort will be used for comparison between the new ACLF diagnostic criteria derivated from the CATCH-LIFE investigation cohort with existing ones. Moreover, future proteomic and metabolic omics analyses will provide valuable insights into the mechanics of ACLF, which will promote the development of specific therapy that leads to decrease patients' mortality. Registration: NCT03641872 .